Mitogen-activated protein kinases and Hedgehog-GLI signaling in cancer: A crosstalk providing therapeutic opportunities?. (December 2015) - Rovida, Elisabetta; Stecca, Barbara
Abstract: The Hedgehog-GLI (HH-GLI) signaling is of critical importance during embryonic development, where it regulates a number of cellular processes, including patterning, proliferation and differentiation. Its aberrant activation has been linked to several types of cancer. HH-GLI signaling is triggered by binding of ligands to the transmembrane receptor patched and is subsequently mediated by transcriptional effectors belonging to the GLI family, whose function is fine tuned by a series of molecular interactions and modifications. Several HH-GLI inhibitors have been developed and are in clinical trials. Similarly, the mitogen-activated protein kinases (MAPK) are involved in a number of biological processes and play an important role in many diseases including cancer. Inhibiting molecules targeting MAPK signaling, especially those elicited by the MEK1/2-ERK1/2 pathway, have been developed and are moving into clinical trials. ERK1/2 may be activated as a consequence of aberrant activation of upstream signaling molecules or during development of drug resistance following treatment with kinase inhibitors such as those for PI3K or BRAF. Evidence of a crosstalk between HH-GLI and other oncogenic signaling pathways has been reported in many tumor types, as shown by recent reviews. Here we will focus on the interaction between HH-GLI and the final MAPK effectors ERK1/2, p38 and JNK in cancer in view of its possible implications for cancer therapy. Several reports highlight the existence of a consistent crosstalk between HH signaling and MAPK, especially with the MEK1/2-ERK1/2 pathway, and this fact should be taken into consideration for designing optimal treatment and prevent tumor relapse.